The impact of wetsuit use on swimming performance, physiology and biomechanics: a systematic review - Gay, A.; Ruiz-Navarro, J. J.; Cuenca-Fernández, F.; López-Belmonte, Ó.; Abraldes, J. A.; Fernandes, R. J.; Arellano, R. (Physiologia, 2022)
This systematic review aims to summarize the effects of wearing different types of wetsuits and swimsuits in front crawl swimming performance and physiological- and biomechanical-related variables. The Web of Science, PubMed, Scopus and the Proceedings of the International Symposium on Biomechanics and Medicine in Swimming databases were searched from inception to 25th March 2022. From the 1398 studies initially found, 26 studies were included in the review. The quality assessment and inter-rater reliability between researchers were conducted. The full body was the most studied wetsuit, with its use allowing 3.2-12.9% velocity increments in distances ranging from 25 to 1500 m, in incremental tests, in 5 and 30 min continuous swimming and in open water events. The sleeveless long vs. the full-body wetsuit led to a 400-800 m performance enhancement. Higher stroke rate, stroke length and stroke index were observed while using three different covered body part wetsuits vs. a regular swimsuit, with a lower energy cost being observed when swimming with the full-body wetsuit compared to a swimsuit. These findings provide useful information for coaches, swimmers and triathletes about the full-body and sleeveless long/short wetsuit use, since these three wetsuits allow improving swimming performance in different distances in diverse aquatic environments.